Improving Classroom Climate of Islamic Junior Secondary Schools and Senior High Schools in West Sumatera - Hadiyanto Hadiyanto; Syahrul Ramadhan; Sulastri Sulastri; Tia Ayuningrum; Singgih Ginanjar; Yeni Resisca; Rini Aprilianda; Pramudia Yordi Hermawan (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2022)
This study aims to help teachers improve the quality of learning by improving the classroom climate, increasing their ability to carry out classroom action research and writing research articles. This article was written as a report of activities that have been carried out to improve classroom climate, including: 1) preliminary study to ensure the need for improvement in class climate, 2) initial assessment (assessment) to capture classroom climate, 3) Provide feedback to teachers and principals about the difference between the actual classroom climate and the preferred climate of the class (preferred climate) by students, 4) Proposing steps to improve the classroom climate as desired by students. The results showed that in general the actual climate of the class was lower than the preferred climate of the students. However, several scales such as competition, difficulty, and bullying in the preferred climate are generally lower than those experienced by students (actual climate). For this reason, treatment steps are needed to make these scales match what students want.